Effects of increasing standardized ileal digestible lysine:calorie ratio on the growth performance of growing-finishing pigs - Bergstrom, J. R.; Shelton, N. W.; Papadopoulos, G.; Potter, M. L.; Jacela, J. Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,080 pigs (PIC TR4 × 1050) were used in four 28-d experiments to determine the lysine requirements of growing-finishing pigs reared in the new Kansas State University finishing barn. Low- and high-lysine corn-soybean meal-based diets with no added fat were formulated for each experiment by varying the amounts of corn, soybean meal, L-lysine HCl, DL-methionine, and L-threonine. Six lysine levels were evaluated in each experiment, with intermediate lysine levels obtained by blending the low- and high-lysine diets. There were 6 pens containing an equal number of barrows and gilts for each treatment, with 6 or 8 pigs per pen. Pens were blocked by initial count and BW. In Exp. 1, 252 pigs (initially 80.7 lb) were fed diets with standardized ileal digestible lysine:calorie (SID lys:cal) ratios of 2.09, 2.39, 2.69, 2.99, 3.29, or 3.59 g/Mcal ME. Increasing the SID lys:cal ratio improved (linear; P < 0.04) ADG and F/G. Optimum performance and income over feed cost (IOFC) was observed at 2.69 g SID lys/Mcal, or a dietary level of 1.01% total lysine and 0.90% SID lysine. In Exp. 2, 288 pigs (initially 122.9 lb) were fed diets with SID lys:cal ratios of 2.12, 2.35, 2.58, 2.81, 3.04, or 3.27 g/Mcal. Increasing the SID lys:cal ratio tended (quadratic; P < 0.12) to increase ADG and improved (linear; P < 0.02) F/G. Optimum performance and IOFC was observed at 2.35 g SID lys/Mcal, or a dietary level of 0.88% total and 0.78% SID lysine. In Exp. 3, 252 pigs (initially 177.2 lb) were fed diets with SID lys:cal ratios of 1.49, 1.79, 2.09, 2.39, 2.69, or 2.98 g/Mcal. Increasing the SID lys:cal ratio tended (linear; P < 0.06) to improve ADG and improved (linear; P < 0.001) F/G. Optimum performance and IOFC was observed at 2.09 g SID lys/Mcal, or a dietary level of 0.80% total and 0.70% SID lysine. In Exp. 4, 288 pigs (initially 224.3 lb) were fed the same SID lys:cal ratios as in Exp. 3. Increasing the SID lys:cal ratio decreased (linear; P < 0.04) ADFI, F/G, carcass yield, and IOFC. Despite a linear improvement in F/G, ADG did not improve above 1.79 g SID lys/Mcal, which resulted in the best IOFC. This requirement is equivalent to 0.69% total and 0.60% SID lysine. These experiments agree with previous recommendations for growing-finishing pigs of this genotype. For pigs weighing 80 to 143 lb, 123 to 190 lb, 177 to 235 lb, and 224 to 284 lb, growth performance and IOFC were optimal with SID lys:cal ratios of 2.69, 2.35, 2.09, and 1.79 g SID lys/Mcal ME (or 0.90%, 0.78%, 0.70% and 0.60% SID lysine) in corn-soybean meal diets without added fat.
Keywords: Income over feed cost; Lysine; Swine